2008
DOI: 10.1111/j.1365-2753.2008.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of educational outreach to improve evidence‐based prescribing in Medicaid: a cautionary tale

Abstract: Among this Medicaid population at high risk for cardiovascular events, an academic detailing programme to increase statin prescriptions was not effective. To assist others to learn from our failed effort, we identify and discuss critical elements in the design and implementation of the programme that could account for these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Demonstrating the effectiveness of interventions to improve the appropriate use of polypharmacy in older patients is hardly achievable in clinical practice, especially when performing educational meetings/workshops, which can have small or even unproven benefit . In fact, the latest Cochrane review concluded that ‘ It is unclear whether interventions to improve appropriate polypharmacy , such as pharmaceutical care , resulted in clinically significant improvement ’ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demonstrating the effectiveness of interventions to improve the appropriate use of polypharmacy in older patients is hardly achievable in clinical practice, especially when performing educational meetings/workshops, which can have small or even unproven benefit . In fact, the latest Cochrane review concluded that ‘ It is unclear whether interventions to improve appropriate polypharmacy , such as pharmaceutical care , resulted in clinically significant improvement ’ .…”
Section: Discussionmentioning
confidence: 99%
“…In the recent past, administrative databases have been largely used to estimate the prevalence of DDIs as well as to determine possible predictors/determinants of DDI occurrence, especially in elderly under poly‐therapy . However, only a limited number of studies have attempted to assess the impact of educational campaigns to improve appropriateness of clinicians' prescriptions, with a non‐significant effect of educational outreach programmes on the prescribing rate of potential DDIs .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from studies of approaches to improving adequacy and/or promoting the reduction or abandonment of low-value pharmacological prescribing shows, on the one hand, that training in isolation does not have an effect in terms of de-implementing inappropriate prescribing. On the other, multi-component interventions that combine multiple tailored interventions (audit and feedback, alert systems and clinical decision support systems) have achieved more positive results [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous systematic reviews reported that passive interventions, such as including unsolicited mailings, are not as effective as active interventions, such as academic detailing. 34,[38][39][40][41][42] No previously published subject reviews have examined the comparative effectiveness of various types of printed materials alone. The purpose of this review is to evaluate the effectiveness of mailed intervention programs that used primarily printed techniques and identify factors that have been associated with successful outcomes.…”
Section: S U B J E C T R E V I E Wmentioning
confidence: 99%